Rational use of water resources (On the example of Karakul district) - Hayitov Yozil Kasimovich; Sherkulov Khurshid Jamshid oglu; Shokirov Akobir Abrorovich (Zien Journals, 2022)
The article describes the rational and efficient use of existing water bodies in Karakul district of Bukhara region and their hydrological features. In addition, a study of the order of water use in the district, the structure of the network, the system of ditches was conducted in collaboration with relevant organizations.
Keywords: Water quantity; water consumption; Amu-Karakol; Gurdush